2010
DOI: 10.4103/0972-6748.90342
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support and life satisfaction in persons with somatization disorder

Abstract: Background:Life satisfaction and perceived social support been shown to improve the well-being of a person and also affect the outcome of treatment in somatization disorder. The phenomenon of somatization was explored in relation to the perceived social support and life satisfaction.Aim:This study aimed at investigating perceived social support and life satisfaction in people with somatization disorder.Materials and Methods:The study was conducted on persons having somatization disorder attending the outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
(13 reference statements)
5
15
0
Order By: Relevance
“…In the present study, majority of persons with somatoform disorder were Muslims, belonging to rural background, married, un-employed and of lower socio-economic status. These findings are similar to those found in a previously conducted study by Arif Ali et al 11 Similar findings are also reported by Barskey 18 who observed that somatization is more common among those who are of lower socioeconomic status, of rural background and among ethnic groups that discourage the direct expression of emotional distress.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, majority of persons with somatoform disorder were Muslims, belonging to rural background, married, un-employed and of lower socio-economic status. These findings are similar to those found in a previously conducted study by Arif Ali et al 11 Similar findings are also reported by Barskey 18 who observed that somatization is more common among those who are of lower socioeconomic status, of rural background and among ethnic groups that discourage the direct expression of emotional distress.…”
Section: Discussionsupporting
confidence: 92%
“…The mean age of persons with somatoform disorder was 40.55 (SD=9.85) years. Another study 11 found the mean age of persons with somatoform disorder to be 42.33 (SD=6.13) years.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Severity in somatization and hyperactive‐impulsive symptoms were also highly ranked predictors ; regressions revealed a positive relation with MSPSS‐ f . High levels of somatization have been frequently found in people with low emotional expression ability [Ali et al, ]. Somatization has been suggested to play a social learned role as an elicitor of interpersonal rewards [Barsky & Klerman, ].…”
Section: Discussionmentioning
confidence: 99%